Unique knowledge, unique skills, unique role: Aboriginal and Torres Strait Islander Health Workers in Queensland, Australia. Issue 7 (2nd July 2021) - Topp, Stephanie M; Tully, Josslyn; Cummins, Rachel; Graham, Veronica; Yashadhana, Aryati; Elliott, Lana; Taylor, Sean
Abstract : Aboriginal and Torres Strait Islander Health Workers (A&TSIHWs) are a professional cadre of Australian health workers typically located in primary care clinics. The role is one of only two that is 'identified'— that is, it must be occupied by an Aboriginal and/or Torres Strait Islander person — and holds specific responsibilities in relation to advocating for facility-level cultural safety. However, lack of understanding of the distinctive skills, scope and value associated with the A&TSIHW role remains pervasive in the broader health workforce. Positioned to represent the perspective of those working as A&TSIHWs, and drawing on 83 in-depth interviews with A&TSIHWs and others, this qualitative study reports on the core functions and distinctive orientation of the role, and seeks to articulate its distinctive value in the modern Queensland health service. Findings highlight the multifaceted (generalist) nature of the A&TSIHW role, which comprises three core functions: health promotion, clinical service and cultural brokerage. Underpinning these cross-cutting functions, is the role's unique orientation, defined by client-centredness and realised through Indigenous strengths based ways of knowing, being and doing. The findings highlight how the A&TSIHW role is one of the only mechanisms through which Aboriginal and Torres Strait Islander knowledge can be brought to bear on context-specific adaptations to routine health service practices; and through which the impacts of lack of cultural or self-awareness among some non-Indigenous health professionals can be mitigated. The complexity of such work in a government health system where a dominant biomedical culture defines what is valued and therefore resourced, is under-recognised and undervalued and contributes to pressures and stress that are potentially threatening the role's long-term viability.